Perancangan Sistem Informasi Administrasi Keuangan Berbasis Web di Kantor Desa Hameli Ate - Rofinus Bali Mema; Vinsensius Aprila Kore Dima; Emirensiana Dappa Ege (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Financial administration plays a crucial role in village-level governance, requiring transparency, accountability, and efficiency in the use of public funds. Currently, the Hameli Ate Village Office still relies on manual methods to manage its financial administration, including recording cash receipts and expenditures using notebooks and simple spreadsheets. This approach presents various issues, such as the risk of data loss, calculation errors, delays in report preparation, and difficulties in tracking and collecting financial transaction data. This study aims to develop a web-based financial administration information system to assist village officials in managing financial data more effectively, efficiently, and in an integrated manner. The methods applied include observation, interviews, and document collection to understand system requirements, while the system development process is implemented using the Waterfall model, which consists of the stages of analysis, design, implementation, testing, and maintenance. The system was built using the PHP programming language and a MySQL database and is designed to generate financial reports automatically and in real time. The testing results show that the system can handle income and expenditure data more quickly, accurately, and in a user-friendly manner. With the implementation of this information system, the financial administration process at the Hameli Ate Village Office becomes more transparent, accountable, and facilitates data-driven decision-making.